2003
DOI: 10.2223/jped.939
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life survey about children and adolescents with juvenile idiopathic arthritis

Abstract: ResumoObjetivo: estudar o impacto da artrite crônica na qualidade de vida relacionada à saúde, por meio de dois instrumentos autoaplicáveis: a versão destinada aos pais do Childhood Health Assessment Questionnaire (CHAQ) e do Child Health Questionnaire (CHQ) PF50 ® .Método: os dois questionários foram respondidos por 36 pais, após instruções durante 1 a 2 visitas clínicas, sendo os índices da Capacidade Funcional (CHAQ), Físico e Psicossocial (CHQ) comparados com as medidas essenciais de atividade da doença: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…Many studies use proxy reporting (14,25,26), whereas other studies have shown that self-reporting appears to be more reliable (20,27) for evaluating HRQOL. Different HRQOL questionnaires, both generic and disease specific, have been used for children with JIA.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies use proxy reporting (14,25,26), whereas other studies have shown that self-reporting appears to be more reliable (20,27) for evaluating HRQOL. Different HRQOL questionnaires, both generic and disease specific, have been used for children with JIA.…”
Section: Introductionmentioning
confidence: 99%
“…También se puede evaluar la capacidad funcional y calidad vida; para ello el más utilizado y validado de manera internacional es el CHAQ (Chilhood Health Assesment Questionnaire) de fácil aplicación adaptado y validado en niños de habla hispana, y comprende la evaluación de aspectos físicos: incluyendo el deterioro de funciones, los síntomas y el dolor causado por la enfermedad o por su tratamiento; aspectos psicológicos: cubriendo un amplio rango de estados emocionales y funciones cognitivas e intelectuales; y aspectos sociales: haciendo hincapié en el aislamiento social y en la autoestima asociados al papel social 12,13 .…”
Section: Introductionunclassified
“…Thus, every child has the right to a good quality of life and to have their needs met. However, it is emphasized that the quality of living standards are often not respected, hence the importance of the evaluation of the child's QOL, especially the ones that have an associated pathology [4,5].…”
Section: Introductionmentioning
confidence: 99%